Teaching International Relations in a Time of Disruption
XV, 165 p. 1 illus.
Keywords: This volume asks how we, as International Relations scholars, support our students, and indeed each other, to create classroom spaces that foster the critical curiosity and engagement required to understand and live in a world that feels dangerously disrupted? In an era of globalization, disruption, and pandemic, International Relations educators need to reflect upon how teaching helps constitute the discipline and position our students to contribute to the advancement of International Relations as a discipline and practice. Through exploring innovative approaches to teaching and learning, this volume ensures that International Relations keeps up with the contemporary needs of students and student learning, and takes advantage of the opportunity to advance as a discipline now and in the future. As we move through ‘pivots’ online and ‘transitions’ to remote learning in the midst of a pandemic, the need for attention to student learning is only made more prescient and urgent. Heather A. Smith is Professor of Global and International Studies at the University of Northern British Columbia. She is the recipient of the 3M National Teaching Fellowship (2006), the Canadian Political Science Excellence in Teaching Award (2012), and a two-time recipient of the UNBC Excellence in Teaching Award. David J. Hornsby is a Professor of International Affairs and the Associate Vice-President (Teaching and Learning) at Carleton University, Ottawa. Published in both the biological and social sciences, he is also a recognized lecturer having received the Faculty of Humanities and Vice-Chancellor's Teaching Award (2013), Wits University, South Africa.